1969
DOI: 10.1083/jcb.41.1.312
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Biochemical Changes in Brown Fat in Cold-Exposed Rats

Abstract: During the first 3 days of exposure of rats to 5°C, the nitrogen concentration of interscapular brown fat increased by 50% and remained at this elevated level for the duration of the 8-wk observation period, while the mass of tissue increased fourfold. The concentration of both DNA and RNA per unit nitrogen reached a maximum after 3 days, then declined; however, the total quantity of each continued to rise. The concentration of various respiratory enzymes decreased during the first few days and then increased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1972
1972
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…1B and 1C). Thomson et al reported that a reduction in fat droplet size in BAT was observed during the first 3 d of stimulation by cold and was followed by a gradual increase in size over a 6-wk period (15). In our study, BAT changed to a reddish and dark color after exposure to cold (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…1B and 1C). Thomson et al reported that a reduction in fat droplet size in BAT was observed during the first 3 d of stimulation by cold and was followed by a gradual increase in size over a 6-wk period (15). In our study, BAT changed to a reddish and dark color after exposure to cold (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The organized elements of the granular endoplasmic reticulum shown by the electron microscope have been overlooked by many authors. THOMSON et al (1969) reported, however, that, in the immature brown fat cells, both the granular and agranular endoplasmic reticulum were found in considerable amounts, but none were seen in large mature cells. To the contrary, almost all investigators noticed numerous free ribosomes widely distributed singly or grouped into rosette-like clusters.…”
Section: Electron Microscopic Observationsmentioning
confidence: 99%
“…25). He further showed that cytolysomes occurred far more frequently in the brown fat cells of the April bat; especially those containing a degenerating mitochondrion were found THOMSON et al (1969), closely packed mitochondria October (fat repletion stage) (Fig. 19).…”
Section: Electron Microscopic Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold adaptation is closely related to an increase in the amount of brown adipose tissue (BAT) and mitochondria [1][2][3]. In addition to the role of fatty acid as the major fuel during cold exposure, recent studies have indicated that BAT plays an important role in regulating blood glucose concentration after a carbohydrate load, especially in coldacclimated rats [4,5].…”
Section: Introductionmentioning
confidence: 99%